Comparison of cardiovascular risk factors, gastrointestinal and musculoskeletal complications in different patterns of shift work in tile industry - mohammadhosein Davari; amirhoshang Mehrparvar; mehrdad Mostaghaci; maryam Bahaloo; mahnaz Poorshafiee (طب کار)
Background: shift work may lead to different health problems due to circadian rhythm. The pattern of shift work, forward or backward, and the duration of each shift period may affect complications. This study was designed to assess and compare the health complications of different patterns of shift work in tile industry. Methods: this cross-sectional study was conducted on 203 shift workers in 2011 in two tile industries in Yazd with different patterns of shift work: on group with fore ward and short term pattern (2morning 2afternoon 2night) and the other with backward and long term pattern (2night 2afternoon 2morning). Data was collected by a questionnaire including occupational and health information such as physical examination and biochemical tests. Results: the frequency of cardiovascular symptoms and hypertension was significantly lower in the first group. The difference in smoking, obesity and abnormal FBS between two groups was not significant. Gastrointestinal symptoms such as dyspepsia, heartburn and constipation were significantly higher in the second group. Joint pain and muscle spasm were significantly lower in the first group. Conclusion: results show a significant difference in cardiovascular, gastrointestinal and musculoskeletal symptoms between forward and backward shift work pattern.